Rola podatkowej tarczy amortyzacyjnej w kształtowaniu wartości przedsiębiorstwa - Kudela, Piotr (Depreciation Tax Shield and Firm Value Shaping, 2006)
Depreciation tax shield decreases the amount of income tax paid, thus affects the level of economic firm value. The problem may be considered from the operational activity point of view or together with taking capital structure into consideration. The former way requires analysis of another tan of no debt tax shield, a tax loss. The latter one in addition needs consideration of interest tax Add and some relationships between different types of tax shields. The level of firm's profitability t also crucial to that analysis. Formula for calculating economic firm value has been transformed subtly in order to emphasize the meaning of tax shields (including the depreciation one) in shaping tit value.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 383-393